THE RELATIONSHIP OF UNDERSTANDING OF ISLAMIC BUSINESS ETHICS AND THE BEHAVIOR OF MUSLIM TRADERS IN THE CONGKO PEOPLE'S MARKET BAREBBO DISTRICT BONE REGENCY - RATIH MUSAHIR; Muh. Hasbi Ash. Shiddiq (Islamic Economic and Business Journal, 2021)
This study discusses the relationship between understanding Islamic business ethics and the behavior of Muslim traders in the Conko People's Market Barebbo District Bone Regency. The purpose of this study was to determine the relationship between understanding Islamic business ethics and the behavior of Muslim traders in Pasar Rakyat Conko Barebbo District Bone Regency and to find out how big the coefficient of determination is for understanding the relationship between understanding Islamic business ethics and the behavior of Muslim women traders in Pasar Rakyat Conko Barebbo District Bone Regency. This study uses a type of field research (Field Research) with a quantitative approach. The number of population and samples in this study were 80 respondents. Data was collected using a questionnaire distributed to each Muslimah trader. The results of the research and discussion show that 1) There is a significant positive relationship between the understanding of Islamic business ethics and the behavior of Muslim traders in the People's Market of Congko Barebbo District Bone Regency from the results of the calculation of the product moment correlation shows ???? !"#$% 0.530  ???? #'()* 0.220. The test results show that the significance value obtained is 0.000 0.05 which means the significance value obtained is smaller than the specified probability . So H0 is rejected and Ha is accepted. 2) The coefficient of determination of the relationship between understanding of Islamic business ethics and the behavior of Muslim traders is 28.1% and the remaining 71.9% is determined by other variables factors such as religiosity, business competition, and level of education also influence the behavior of Muslim traders.